Preliminary Study on Potential Bacterial Species Introducing Antibacterial Agent from Sponge in Unggeh Island Central Tapanuli, Indonesia - Latifah Ningrum Abdillah; Dwi Suryanto; Kiki Nurtjahja; Jendri Mamangkey (Jurnal Penelitian Pendidikan IPA, 2024)
Sponges have the potential to symbiont with bacteria that produce antibacterial compounds. This study was conducted to isolate and test the antibacterial activity of sponge symbiont bacteria. Bacterial isolates obtained were tested for antibacterial activity against Staphylococcus aureus, Bacillus subtilis and Escherichia coli using the Kirby-Bauer method. The identification results of both sponges have similarities with Clathria sp. and Hyrtios sp. symbiont bacteria obtained from both sponges as many as 16 isolates. Antibacterial activity testing had a weak inhibitory effect on isolates Sp1A, Sp2C, Sp2D and Sp2F, while Sp2J showed moderate inhibition against gram-negative and positive bacteria. The antibacterial activity of the whole supernatant of symbiont bacteria obtained the diameter of the inhibition zone with weak, medium and strong categories. Sp1A isolate supernatant was obtained, potentially able to fight Escherichia coli bacteria with a strong category as a representation of gram-negative bacteria and against gram-positive bacteria (Bacillus subtilis, Staphylococcus aureus) classified into the medium category. In conclusion, 16 symbiont bacterial supernatants have antibacterial activity mostly active against gram-negative bacteria Escherichia coli and gram-positive bacteria Bacillus subtilis. There are 6 isolates (Sp1A, Sp1B, Sp1E, Sp1F, Sp2D, Sp2F) active as antibacterial against Staphylococcus aureus with weak and moderate categories.